Environmental, social and health dimensions of food supply policies and proposals in Brazil - Souza PEREIRA, Douglas; RECINE, Elisabetta (Revista de Nutrição, 2023)
Objective To analyze the presence and characteristics of social, environmental and health dimensions identifi ed in the current national food supply policy proposals and policies. Methods This is a study with a qualitative approach using a documentary analysis technique referring to the period between 2003 and 2015, in addition to the Agricultural Policy of 1991. Results The results of the analyzes of the documents of the Federal Executive Power and the Public Policy Councils are similar, policies that seek alternatives to the negative impacts of the hegemonic model of food supply, different from the document of the Federal Legislative Power and Agricultural Policy, which superfi cially approach alternatives to these impacts, or are limited to strengthening the dominant productive system. Conclusion Thus, a national food supply policy is needed for the planning of actions, considering social, environmental and health impacts and taking as reference the initiatives already built by sectors of the Executive Power and by the Public Policy Councils.